2021
DOI: 10.1108/jaar-12-2019-0164
|View full text |Cite
|
Sign up to set email alerts
|

The International Financial Reporting Standards 9 financial instruments, information quality and stock returns in the modern technology era

Abstract: PurposeThis paper investigates the relationship between information quality and stock returns during the International Financial Reporting Standards (IFRS 9) pre-adoption announcements and examines the influence of modern technology on these relationships across 24 emerging countries.Design/methodology/approachThis paper conducts an event study using data obtained from the DataStream, Osiris, International Telecommunication Union (ITU) and the World Bank databases from 2009 to 2014. The non-linear generalized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…However, if a corporation surveyed many accountants and summed up their responses, it would appear impartial and objective. The degree of error-freeness describes the degree to which information is error-free (Balios, 2021;ElKelish, 2021).…”
Section: Fundamental Qualitative Characteristicsmentioning
confidence: 99%
“…However, if a corporation surveyed many accountants and summed up their responses, it would appear impartial and objective. The degree of error-freeness describes the degree to which information is error-free (Balios, 2021;ElKelish, 2021).…”
Section: Fundamental Qualitative Characteristicsmentioning
confidence: 99%
“…The common law system, however, provides better support for corporate transparency, investor protection and International Financial Reporting Standards (IFRS) adoption (Bushman et al, 2004;La Porta et al, 1998;Zehri and Chouaibi, 2013). Klapper and Love (2004) found that firm-level governance is, on average, low in weak legal systems, whilst other studies have found that a codified legal system has a positive impact on stock returns across emerging countries (ElKelish, 2021). Law enforcement such as the rule of law and control of corruption reflects the extent of confidence and acceptance of societal rules, contract enforcement quality, property rights, the courts, crime and violence prospects (Armstrong et al, 2010;Kaufmann et al, 2011;Drobetz and Momtaz, 2020).…”
Section: Characteristics Of Firms' External Environmentmentioning
confidence: 99%